Elevated 5hmC levels characterize DNA of the cerebellum in Parkinson’s disease - Reinhard Stöger; Paula J. Scaife; Freya Shephard; Lisa Chakrabarti (npj Parkinson's Disease, 2017)
Abstract 5-methylcytosine and the oxidation product 5-hydroxymethylcytosine are two prominent epigenetic variants of the cytosine base in nuclear DNA of mammalian brains. We measured levels of 5-methylcytosine and 5-hydroxymethylcytosine by enzyme-linked immunosorbent assay in DNA from post-mortem cerebella of individuals with Parkinson’s disease and age-matched controls. 5-methylcytosine levels showed no significant differences between Parkinson’s disease and control DNA sample sets. In contrast, median 5-hydroxymethylcytosine levels were almost twice as high (p < 0.001) in both male and female Parkinson’s disease individuals compared with controls. The distinct epigenetic profile identified in cerebellar DNA of Parkinson’s disease patients raises the question whether elevated 5-hydroxymethylcytosine levels are a driver or a consequence of Parkinson’s disease.